The relationship between the brain and spirituality with respect to aging and neurodegenerative diseases: clinical and research implications. Issue 4 (1st October 2020) - Datta, Saachi; Newberg, Andrew
ABSTRACT: This article reviews and synthesizes the current data on the relationship between the brain and religion and spirituality, with regard to aging and neurodegenerative diseases. Specifically, we consider how religious and spiritual beliefs, attitudes, and practices might be affected by the aging process on the brain, particularly when neurodegenerative diseases occur. Various practices such as meditation or prayer also are associated with brain processes and such a relationship could have clinical implications for the use of these practices to help the elderly improve anxiety, depression, or cognition. Finally, we consider potential negative relationships such as religious struggle that can be part of the relationship between the brain and religious or spiritual beliefs as people age. In the end, it is hoped that this neurotheological approach, combining an understanding of brain processes with religious and spiritual phenomena, can be useful in deepening our knowledge regarding the impact of aging and neurogenerative diseases on brain function, and concomitantly on religiousness and spirituality in the elderly population.